Psychosocial and Spiritual Model as the Analgesic for Patients with Terminal Illness - Samuel, IORKOSU, Tyover; Mohammed, Sadiq Abubakar; David, Ishor, Gever (Journal of Medical Genetics and Clinical Biology, 2024)
Terminal illnesses are quite painful and thus require proper attention both from the healthcare personnel and the family. The modern developments in therapeutic and care options in trying to reduce the effects of terminal illness have contributed a lot in the rise of the quality of health care among diagnosed patients. Through the procedure, a person may feel frightened and also anxious. This worry has been documented in patients with life-threatening diseases such as cancer, bubonic plague, or dynamic coronary infarction. Stress in between scientific research and belief are much more frequently revealed in western culture. Terminal illnesses are quite painful and thus require proper attention both from the healthcare personnel and the family. This work tries to figure out how people cope with terminal illnesses, emphasizing the importance of the psychosocial and spiritual model in helping patients who have been diagnosed with these kinds of diseases. It was found that only a small number of patients with terminal illness were receiving support from healthcare personnel. This of course suggests that there is limited availability of psychosocial personnel to handle the emotional and spiritual suffering of patients with terminal illness. In the absence of professional health services, patients may sought the support of family and friends. This work tries to figure out how people cope with terminal illnesses, emphasizing the importance of the psychosocial and spiritual model in helping patients who have been diagnosed with these kinds of diseases.